1986
DOI: 10.1149/1.2108651
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Surface Cleaning of Silicon and Its Application to Silicon MBE

Abstract: A low temperature thermal cleaning method for Si molecular beam epitaxy (MBE) is proposed. This method consists of wet chemical treatment to eliminate carbon contaminants on Si substrates, thin oxide film formation to protect the clean Si surface from contamination during processing before MBE growth, and desorption of the thin oxide film under UHV. The passivative oxide can be removed at temperatures below 800~ It is confirmed that Si epitaxial growth can take place on substrates cleaned by this method and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
433
0
8

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,632 publications
(459 citation statements)
references
References 9 publications
8
433
0
8
Order By: Relevance
“…Surface contamination removal and surface oxidation were performed by using Shiraki's method. 33) We confirmed that the thickness of oxide layer estimated by X-ray photoemission spectroscopy (XPS) is 5.8 Å, and this is consistent with the reported thickness (5-8 Å). 33) The thinness allows electron tunneling, and this indicates the possibility of STM measurement even on an oxide Si surface.…”
Section: Experimental Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Surface contamination removal and surface oxidation were performed by using Shiraki's method. 33) We confirmed that the thickness of oxide layer estimated by X-ray photoemission spectroscopy (XPS) is 5.8 Å, and this is consistent with the reported thickness (5-8 Å). 33) The thinness allows electron tunneling, and this indicates the possibility of STM measurement even on an oxide Si surface.…”
Section: Experimental Methodssupporting
confidence: 89%
“…The observed step height is consistent with the monolayer step one of Si(110), and this indicates that the monolayer step of Si (110) is visible through the oxide layer due to the thinness of the oxide layer formed by Shiraki's method. 33) An increase in the desorption time induces the formation of large circle-shaped voids [ Fig. 1(b)].…”
Section: Resultsmentioning
confidence: 99%
“…After chemically cleaning, the substrates were annealed at 750 °C for 2 h in the MBE chamber to remove the surface oxide, which is the process based on the Shiraki-Ishizaka method [7]. Then Si buffer layer with a thickness of 100 nm was deposited at 750 °C and subsequently SiGe single layer was grown at 500 °C without intentional doping.…”
Section: Methodsmentioning
confidence: 99%
“…This vicinal angle gives o an average terrace size of around 160 A, which was confirmed by the STM results. The Si(001) samples were first degreased and cleaned with a wet-chemical oxide etch-regrowth procedure [21] and mounted on degassed tantalum sample holders before introducing them into the UHV chamber. The samples were degassed in the UHV for approximately 10 h at 680°C by using an e-beam heater.…”
Section: Methodsmentioning
confidence: 99%